Ethical perspectives of employees: a case study of employees of the University of The Witwatersrand - Iroha, George (My University, 2019)
Ethical misconduct is a major challenge in all sector of the economy. Consequently, the private public sectors are introducing measures to minimise the impacts of unethical behaviour in their operations. Universities, which contributes to equipping future leaders in the society, are affected by this challenge. Researchers have identified many unethical practices amongst students, academic and non-academic staff members of tertiary institution in Africa. This study examined key factors in understanding the ethical perspectives of university employees. First it assessed the contributions of external factors such as work environment, economic condition and government legislation, to ethical perspectives of categories of employees in the university. Secondly it analysed the effects of organisational factors such as code of conduct, organisational culture and work environment on ethical decision-making among these employees. Thirdly, the study analysed how individual-level factors such as attitude, peer influences, ego, values and belief, contribute to unethical behaviour of university. Lastly, it assessed the moderating effects of demographic factors on the association between these identified factors and ethical perspectives of university employees. This study found a significant positive association between external factors and ethical perspectives of university employees. It also found a high positive association between individual-level factors and ethical perspectives of employees. The organisational factor included in this analysis showed no significant impact on the ethical perspectives of employees. Age is the only demographic factor included in the study with a significant moderating effect in these associations. These findings should be considered by tertiary institutions in formulating and implementing ethical guidelines that advance their strategic and performance goals
A dissertation submitted to the Faculty of Commerce, Law and Management, at the University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Master of Commerce in the School of Economics and Business Sciences (SEBS), 2019